A comparison of human skeletal muscle cell maturation in 2D versus 3D culture: A quantitative proteomic study - Benjamin R. Tollitt; Samantha W. Jones; Jessica Ohana; James R. Henstock; Malcolm J. Jackson; Anne McArdle (Physiological Reports)
Abstract Compared with 2D monolayers, 3D models more closely mimic native muscle tissue and allow functional measurements. A more complete understanding of how culture conditions and duration affect myotube maturity/function is crucial for validating the transition to 3D systems. Human skeletal muscle cells were cultured as 2D monolayers or within 3D hydrogels for up to 21 days. Quantitative proteomic analysis and functional measurements were conducted to evaluate muscle cell differentiation. Myoblasts differentiated into myotubes by 8 days in both environments; however, at Day 8, 3D constructs exhibited a predominantly slow‐twitch phenotype, compared with the mixed fiber type of 2D monolayers. By Day 21, 3D constructs demonstrated enhanced mitochondrial maturity, extracellular matrix remodeling, and a fast‐twitch phenotype, indicated by increased myosin‐2 abundance (Log2(FC)>1.29, p <0.05). Passive tension increased by >20% following prolonged culture of 3D muscle constructs, but contractile forces reduced by >40%. This study provides a comprehensive proteomic profile of human skeletal muscle cells in 2D and 3D, demonstrating that 3D culture promoted myotube maturity and highlighting the importance of selecting appropriate culture conditions. Data suggest 8 days of differentiation as ideal for achieving peak contractile force in 3D constructs, providing optimal models for testing interventions aimed at preserving muscle function.